Multidexterity: Combining Competing Business Models in Transforming Economies - Demir, Robert; Angwin, Duncan (Management and organization review, 2021)
In an attempt to respond to recent calls for better understanding the coexistence of multiple business models, we develop the concept of ‘multidexterity’ – the ability to develop, nurture, and execute several distinctive BM strategies simultaneously across different levels and functions of the MNC and its host markets. To illustrate this approach, we describe a European healthcare firm entering the rapidly transforming economy of China and facing regulatory constraints and ambiguities in the application of industry standards. This situation is a generic challenge for MNCs entering rapidly transforming economies, which they help in turn to substantially alter and develop. We argue multidextrous business models are effective entry strategies for MNCs. They also help resolve two conceptual limitations in the BMI literature: (1) the problem of environmental contingencies and (2) the interrelatedness of factors at the macro, meso, and micro levels. We address these problems from a practice approach. We provide some implications for the concept of multidexterity and business models and address managerial challenges and prospects in developing multidextrous organizations. 为了响应近期关于更好地理解多种商业模型共存的呼吁，我们开发了“多重敏捷”的概念——在跨国公司及其东道国市场的不同层次和功能上，同时开发、培育和执行几种独特的商业模型(BM)战略的能力。为了说明这种方式，我们描述了一个欧洲医疗健康公司进入快速转型的中国经济，以及面临监管限制和行业标准应用上的含糊不清的情况。这是进入快速转型经济体的跨国公司面临的普遍挑战，而又反过来帮助它们大幅改变与发展。我们认为多重敏捷的商业模式是跨国公司有效的进入策略，也有助于解决BMI文献中两个概念的局限性：(1)环境偶然性的问题，(2)宏观、中观和微观层面因素的相关性。我们以实践的方式来解决这些问题。我们为多重敏捷概念和商业模式提供了一些启示，并探讨了发展多重敏捷组织的管理挑战和前景。 В ответ на призыв улучшить понимание того, каким образом несколько моделей ведения бизнеса могут сосуществовать, мы разрабатываем концепцию «мультидекстрии» – способности разрабатывать, развивать и применять несколько различных стратегий управления бизнесом одновременно на разных уровнях и в разных подразделениях МНК на рынках принимающих стран. С целью проиллюстрировать этот подход, мы рассматриваем европейскую медицинскую компанию, которая вступает в быстро растущую экономику Китая и сталкивается с нормативными ограничениями и неясностью в применении промышленных стандартов. Эта ситуация представляет собой общую проблему для МНК, начинающих работать в странах со стремительно меняющейся экономикой, которую компании, в свою очередь, помогают существенно изменить и развить. Мы утверждаем, что мультидекстральные модели управления бизнесом являются эффективными стратегиями для входа МНК. Они также помогают устранить два концептуальных ограничения в литературе по инновационным моделям ведения бизнеса: (1) проблему непредвиденных обстоятельств во внешней среде и (2) проблему взаимосвязи факторов на макро-, мезо- и микроуровнях. Мы решаем эти проблемы исходя из практического подхода. Мы предлагаем некоторые выводы для концепции «мультидекстрии» и моделей ведения бизнеса, а также рассматриваем управленческие проблемы и перспективы развития мультидекстральных организаций. En un intento para responder a los llamados recientes para entender mejor la coexistencia de múltiples modelos, desarrollamos el concepto de “multidestreza”: la habilidad para desarrollar, nutrir, y ejecutar varias estrategias distintivas de modelos de negocio simultáneamente en diferentes niveles y funciones de la empresa multinacional y sus mercados anfitriones. Para ilustrar este enfoque, describimos una empresa dedicada al cuidado de la salud europea que entra en la economía de China que se transforma rápidamente y que se enfrenta a restricciones regulatorias y ambigüedades en la aplicación de estándares de la industria. Esta situación es un reto genérico para las empresas multinacionales que entran en economías de rápida transformación, que a su vez ayudan a alterar y desarrollar sustancialmente. Sostenemos que los modelos de negocio multidiestros son estrategias de entrada efectiva para las empresas multinacionales. También ayudan a resolver dos limitaciones conceptuales de la literatura sobre innovación en el modelo de negocio: (1) el problema de las contingencias ambientales y (2) la interrelación de los factores a los niveles macro, meso, y micro. Abordamos estos problemas desde un enfoque práctico. Proporcionamos algunas implicaciones para el concepto de multidestreza y modelos de negocio, y abordamos los desafíos y perspectivas de gestión en el desarrollo de organizaciones multidiestras.